ANALYSIS OF THE ENGLISH-LANGUAGE SLOGANS USED BY HIGHER EDUCATION INSTITUTIONS IN WEST JAVA - Krisna Yudha Bakhti; Sri Nur Yuliyawati (Politeknik Negeri Bengkalis, 2019)
This study analyzes the English-language slogan used by higher education institutions in West Java. The purpose of this study is to describe the linguistic patterns and to describe the substance contained in the slogans. This research used descriptive method in analyzing data since it was aimed to get a picture of the use of slogans in higher education institutions. The data were 63 English-language slogans of higher education institutions in West Java with the official web pages and electronic brochures on the Internet as data resources. This study shows that the English-language slogans used by higher education institutions in West Java consist of phrases and sentences. These phrases are noun phrase (41 or 64% slogans), gerund phrase (6 or 9.2 % slogans), verb phrase (4 or 6.3% slogans), prepositional phrase (3 or 4.7% slogans), and infinitive phrase (1 or 1.5% slogan). Meanwhile, the types of the sentence are declarative sentence (8 or 12.5 % slogans) and imperative sentences (1 or 1.5% slogans). This study also shows that there are 13 slogans (20.9%) which contain goal, 49 (77.8%) slogans which contain ideology, and 1 (1.6%) slogan which contains both goal and ideology.